Convergence theorems for maximal monotone operators, weak relatively nonexpansive mappings and equilibrium problems - Nammanee K. (2014)
We introduce hybrid-iterative schemes for solving a system of the zero-finding problems of maximal monotone operators, the equilibrium problem, and the fixed point problem of weak relatively nonexpansive mappings. We then prove, in a uniformly smooth and uniformly convex Banach space, strong convergence theorems by using a shrinking projection method. We finally apply the obtained results to a system of convex minimization problems. Copyright © 2012 Kamonrat Nammanee et al.